Pemetaan Sebaran Puri di Kota Denpasar dan Kabupaten Badung Menggunakan Sistem Informasi Geografis Berbasis Web dengan Metode ADDIE - Gusi Ketut Ayu Rahayu Wijayanti; Kadek Oky Sanjaya; I Putu Mahendra Adi Wardana (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2026)
The rapid development of information technology, particularly in the use of Geographic Information Systems (GIS), provides significant opportunities for preserving cultural heritage. One example is the palaces in the Denpasar City and Badung Regency areas, which have high historical and cultural value, but their existence is increasingly threatened by urban development and the lack of available information. This study aims to map the distribution of palaces using web-based GIS as an effort to preserve and disseminate information to the wider public. The system was developed using the ADDIE method, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The system was built with Laravel 11, PHP 8.2, a MySQL database, and uses the Leaflet.js interactive map. The result of this study is a palace mapping website that allows the public to access location information and the history of palaces interactively without having to log in, and provides data management rights for admins. The system's main features include an admin dashboard, palace data management, interactive maps, location search, and integration with Google Maps. The testing phase was carried out using the Black Box method to describe the system's performance according to the designed functionality. This research is projected to support the preservation of the palace as a Balinese cultural heritage and become a reference in the documentation of other cultural sites.